Policy Note: Policy Responses to Ensure Access to Water and Sanitation Services During COVID-19: Snapshots from the Environment for Development (EfD) Network - Amaechina, Ebele; Amoah, Anthony; Amuakwa-Mensah, Franklin; Amuakwa-Mensah, Salome; Bbaale, Edward; Bonilla, Jorge A.; Brühl, Johanna; Cook, Joseph; Chukwuone, Nnaemeka; Fuente, David; y 9 autores más (2020)
This policy note provides a snapshot of water and sanitation measures implemented by governments in response to the COVID-19 pandemic in 14 countries in the Global South: Costa Rica, El Salvador, Guatemala, Honduras, Nicaragua, Chile, Colombia, Ghana, Kenya, Nigeria, Panama, South Africa, Uganda and Vietnam.We find thatmany countries have taken action to stop utility disconnections due to non-payment. With the exception of Ghana and Vietnam, few countries are instituting new water subsidy programs, and are instead choosing to defer customers’ bills for future payment, presumably when the pandemic recedes and households will be able to pay their bills. It is easier for the utilities’ COVID-relief policies to target customers with piped connections who regularly receive bills. However, the situation for unconnected households appears more dire. Some countries (e.g., Ghana, Kenya, South Africa and Uganda) are attempting to provide unconnected households temporary access to water, but these households remain the most vulnerable. This health crisis has accentuated the importance of strong governance structures and resilient water service providers for dealing with external health, environmental and economic shocks.